High-speed x-ray CT imaging of a strongly cavitating nozzle flow. (19th July 2018) - Bauer, D; Barthel, F; Hampel, U
Abstract: Examining or imaging of internal structures in flows with cavitation is still one of the greatest challenges in this field of research. In a specially designed nozzle, a strong cavitation region (CR) is generated with a liquid core (LC) in the center, surrounded by vapour. While it is almost not feasible to visualize the inside of the CR with visible light, it is shown that with high-speed x-ray computed tomography it is possible to visualize the dynamics of the unsteady cavitational flow structures inside the CR. The observed phenomena start with a ring of cavitation and small amounts of vapour inside the LC at / near the entrance of the cavitation channel. Further downstream the cavitation is growing rapidly and cavitation structures inside the LC can be identified. In addition the results are compared with former time averaged CT images of the same nozzle and with results obtained from high-speed videography.